Empowerment of a community-based coffee shop to develop an entrepreneurial ecosystem through collaboration with stakeholders: An action research approach: An action research approach - Priyono, Anjar; Moin, Abdul; Piper, Ivan (Universitas Ahmad Dahlan, 2024)
This study examines the role of a community-based coffee shop as an entrepreneurial ecosystems that serve as the hub for economic activities among local citizens. Utilizing an action research approach, the community service team engaged directly in the field, facilitating the coffee shop’s collaboration with various stakeholders to foster value creation. The action research methodology involves an iterative process of planning, implementation, evaluation, and reflection, rather than being a one-time intervention. The team worked closely with stakeholders to establish an entrepreneurial ecosystem within the coffee shop venue, aiming to actualize co-value creation. In this context, value creation is collaborative among ecosystem participants and is not merely linear; the coffee shop cannot simply offer products and expect customers to visit. Key stakeholders in this entrepreneurial ecosystem include farmers, government agencies, educational institutions, hobby clubs, training providers, and others. The coffee shop must orchestrate these stakeholders to ensure value creation that benefits the wider community. The enhancement of community economic well-being is evidenced by increased economic activity around the coffee shop area.